answersLogoWhite

0

Take the two equations, and line them up with common terms in the same positions:

x - y = 6

x - 2y = 7

In this case, the operation is quite simple because x has no coefficient in either equation. You can simply subtract each term in the latter equation from it's corresponding term in the prior one:

x - y = 6

x - 2y = 7

___________

0 + y = - 1

So we know that y is equal to negative one, and you can solve for x by simply substituting that -1 into either equation:

x - (-1) = 6

x + 1 = 6

x = 5

So x is equal to five, and y is equal to negative one.

User Avatar

Wiki User

15y ago

What else can I help you with?